Composition and Activity of Copper–Palladium Catalyst on Carbon Fiber Material for Air Purification from Carbon Monoxide - Tatyana Kiose; Tatyana Rakitskaya; Alim Ennan; Volodymyr Vasylechko; Halyna Gryshchouk (Lviv Polytechnic National University, 2023)
A set of research methods (X-ray phase, desorption, kinetic) was used to determine the state of the basic components K2PdCl4 and Cu(NO3)2 in the catalyst for the oxidation of carbon monoxide by oxygen. It was found that the palladium (II) and copper (II) initial compounds under the action of carbon fiber carrier change their state. Palladium is reduced to X-ray amorphous Pd0, and copper (II) is in the form of a crystalline phase Cu2(OH)3Cl. It was found that the catalyst exhibits protective properties within the initial concentrations of carbon monoxide  300 mg/m3 and an effective contact time of 0.45 s and can be used in human respiratory protection.
СКЛАД ТА АКТИВНІСТЬ КУПРУМ- ПАЛАДІЄВОГО КАТАЛІЗАТОРА НА ВУГЛЕЦЕВОМУ ВОЛОКНИСТОМУ МАТЕРІАЛІ ДЛЯ ОЧИЩЕННЯ ПОВІТРЯ ВІД МОНООКСИДУ КАРБОНУ
Keywords: carbon monoxide; carbon fiber materials; catalysts; oxidation; respiratory devices